The role of seasonal factor in congenital abnormality forming - O. V. Antonov; Ye. V. Bogachyova; A. A. Komarova; I. V. Antonova; A. A. Velmatova; G. A. Kovalyova; S. N. Maltsev; K. V. Mitrofanov (Бюллетень сибирской медицины, 2012)
The results of prevalence, structure and timerisk study in children birth with malformations inOmskin the period of 1998—2008 are presented. Birth of children with congenital abnormality weight average index accounted for (47.72 ± 0.66)%. Musculoskeletal and cardiovascular malformations prevailed in birth abnormality total number structure. According to ICD-10 the congenital malformations were united in groups and seasonal variation indices nave been determined for them. Study results indicated the predominance of children conception cases with high risk malformations forming in August, November and December.